Chapter 12 The partial and the vague as a visual mode in Bronze Age rock art - Fahlander, Fredrik (Social Archaeology and Material Worlds, 2020)
Studies of rock art normally depart from a classification of type, style and what the motifs represents or depicts. South Scandinavian rock art, however, is often vague, incomplete and fragmentary. In this chapter, it is argued that certain rock art motifs, mainly boats and anthropomorphs, were deliberately made incomplete as a part of a vitalist technology with the aim of affecting the world. An important aspect of such visual vagueness, intentional or not, is that it can function as a punctum in Roland Barthes's terminology and evoke affect among beholders. The incomplete motifs also stress the making of rock art as a continuous process in which details can be added over time to enhance certain aspects or radically alter the motif. The chapter is illustrated with examples of Bronze Age rock art of the Mälaren district in central-eastern Sweden.